Elevational contrast in predation and parasitism risk to caterpillars in a tropical rainforest. Issue 11 (12th November 2019) - Libra, Martin; Tulai, Salape; Novotny, Vojtech; Hrcek, Jan
Abstract: Invertebrate predators and parasitoids are among the most important natural enemies of insect herbivores. Yet, the strength of natural enemy pressure along an altitudinal gradient and interactions between the groups of natural enemies (such as predation on parasitized prey) are not well known. Various methods are used to reveal the mortality factors of herbivores. Predation pressure is usually assessed through exposure of artificial prey. However, this method cannot provide information about the attacks of parasitoids, or their eventual interactions with predators. Furthermore, artificial or dead prey might not attract predators because they do not show expected host behavior, and this method mostly cannot distinguish between predation and scavenging. For the first time in a tropical rainforest, we quantified elevational contrast in mortality factors using exposure of live caterpillars. We exposed a total of 800 live caterpillars of Talanga excelsalis moresbyensis Strand (Lepidoptera: Crambidae) on saplings of Ficus copiosa Steud. (Moraceae) at two elevations in primary tropical rain forest in Papua New Guinea (200 and 1 200 m a.s.l.). We exposed the caterpillars in two treatments: exposed to and protected from invertebrate predators and parasitoids. Disappearance of caterpillars was significantly higher in the exposed treatment. Furthermore, caterpillar disappearance was significantly higher in lowlands than in highlands (43 vs. 12%). We consider the vast majority of the disappearance to be due to predation, as migration of the caterpillars from the focal trees was not observed (except one caterpillar). This estimate of invertebrate predation rate corresponds with studies which used artificial caterpillar models. No significant difference in parasitism rate between the two elevations was observed (12 vs. 13%). The combination of the disappearance and parasitism rate patterns means that larval parasitoids face stronger pressure from invertebrate predators through higher predation of their hosts in the lowlands than in the highlands. Abstract : Live caterpillars of locally occurring Lepidoptera species were exposed to invertebrate predators and parasitoids at two elevations in primary tropical rain forest in Papua New Guinea. Caterpillar disappearance was significantly higher in the lowlands than in the highlands. The parasitism rate was not significantly different between the two elevations. The combination of disappearance and parasitism rate patterns implies that larval parasitoids face stronger pressure from invertebrate predators through higher predation of their hosts in the lowlands compared to the highlands.